Про методологію розробки програм енергоефективності та енергозбереження і недоліки при їх створенні - Maliarenko O.Ye. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
In the article the critical analysis of existent methodical approaches is given to determination of power efficiency at different levels of management by an economy and methodical and terminology errors, that determinations and prognostications of indexes of efficiency for the programs of energy saving regional and of particular a branch take place in methods.